IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT SIKAP DAN PERILAKU POSITIF SISWA - Meli Gustina (UNISAN JURNAL, 2024)
This study aims to describe and understand education management in school education units and the implementation of education management in improving the education of students' interests, attitudes and behavior at SMP Negeri 32 Bandar Lampung , Negara Batin District, Way Kanan Regency. Methods This research uses a qualitative approach with triangulation data collection techniques. The research location is in the First Middle School Educational Institution of The results showed that the implementation of character education management in developing students' interests, attitudes and behavior was based on objective planning with clear and specific goals, having regular education programs, developing activities in the form of intra-curricular, extracurricular, guidance and counseling of activity programs with the goal is to build character education for students, increase student skills in the practice of humanizing humans and other skills. Determination of character education management in developing students' interests, attitudes and positive behavior. in the form of long-term and short-term programs carried out by example, direction, assignment, habituation, and environment creation. This affects the character of the santri in the form of leadership, discipline, trustworthiness, sincerity and courtesy. These conditions support the creation of an environment that is healthy and conducive learning environment, everything that is heard, seen, and suggested by students are elements of education.